The Influence of Women's Leadership Styles and Conflict Management on Productivity Within The Direct Sales Community of PT. XYZ - Firiana Rahman (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
This study aims to explore the influence of women's leadership styles and conflict management on productivity within the direct sales community of PT. XYZ. The data obtained will be analyzed using descriptive statistics and quantitative analysis. The results of this research are expected to provide recommendations to relevant parties on how to enhance productivity through effective women's leadership styles and good conflict management. The results of the descriptive analysis show that for the Women's Leadership variable, it falls under the "very good" category with a score of 84.49%, while for the Conflict Management variable, it is also classified as "very good" with a score of 33.71%. As for the Productivity variable, it is relatively high with a score of 63.18%. From the hypothesis testing, the conclusion is that women's leadership style and conflict management have a partial influence on the productivity of members in the direct sales community. Based on the results of the coefficient of determination test, it can be determined that the value of R-square is 0.118 or 11.8%. This means that 11.8% of the productivity of the direct sales community is influenced by women's leadership styles and conflict management.